borrowed time : Two Centuries of Booms, Busts, and Bailouts at Citi - Freeman, James
The alarming, untold story of Citigroup--one of the largest financial institutions in the world--from its founding in 1812 to its role in the 2008 financial crisis, and the many near-death experiences in between. -- From Amazon summary